Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $R$ be commutative ring with no (nonzero) nilpotents. If $f(x) = a_0+a_1x+\cdots+a_nx^n$ is a zero divisor in $R[x]$, how do I show there's an element $b \ne 0$ in $R$ such that $ba_0=ba_1=\cdots=ba_n=0$?

share|cite|improve this question
up vote 23 down vote accepted

It is true over any commutative ring, and is sometimes called McCoy's theorem. Below is a proof sketch from my sci.math post on 5/4/2004:

Theorem $\ $ Let $ \,F \in R[X]$ be a polynomial over a commutative ring $ \,R.\,$ If $ \,F\,$ is a zero-divisor then $ \,r\,F = 0\,$ for some nonzero $ \,r \in R.$

Proof $\ $ Suppose not. Choose $ \,G \ne 0\,$ of min degree with $ \,F\,G = 0.\,$

Write $ \,F =\, a +\,\cdots\,+ f\ X^k +\,\cdots\,+ c\ X^m\ $

and $ \ \ \ G = b +\,\cdots\,+ g\ X^n,\,$ where $ \,g \ne 0\:$ and $ \,f\,$ is the highest deg coef of $ \,F\,$ with $ \,f\,G \ne 0\,$ (note that such an $ \,f\,$ exists else $ \,F\,g = 0\,$ contra supposition).

Then $ \,F\,G = (a +\,\cdots\,+ f\ X^k)\ (b +\,\cdots\,+ g\ X^n) = 0.$

Thus $ \,f\,g = 0\,$ so $ \,\deg(f\,G) < n\,$ and $ \, F\,(f\,G) = 0,\,$ contra minimality of $ \,G.\ \ $ QED

Alternatively it follows Gauss's Lemma (Dedekind-Mertens form) or related results.

share|cite|improve this answer
Why does this imply that F(fG)=0? I understand that FG = 0 but why does this say something about the effect of F on the polynomial fG with deg(fG) < deg(G)? – mathjacks Sep 7 '14 at 15:54
$F(fG)=0$ follows from $FG=0$. The discussion before was needed in order to ensure that $\deg(fG)<\deg(G)$. – Martin Brandenburg Sep 27 '14 at 13:51
Thanks, very nice proof. – Pham Hung Quy Dec 14 '14 at 14:10
Bill, what an elegant proof! Thanks for sharing this lovely argument. – Prism Jun 26 '15 at 20:43
@user95553 While $\,fg =X^7 - X = 0\,$ as a polynomial function on $\,\Bbb Z_7,\,$ it is not true that $\,X^7-X = 0\,$ as formal polynomials $\in \Bbb Z_7[X].\,$ Formal vs. functional polynomials is discussed in many prior answers, e.g. this one. – Bill Dubuque Aug 23 '15 at 15:07

Assume that $gf=0$ for some $g\in R[X]$ and let $c$ be the leading coefficient of $g$. Then $ca_n=0$. Therefore $cf$ is either $0$ (in which case $c$ is your $b$), or $cf$ has degree less than $n$ with $g(cf)=0$. Proceed by induction on $n$. In the end you find that some power of $c$ kills every $a_i$, and $c$ was not nilpotent ...

share|cite|improve this answer

Apparently, Bill Dubuque's argument is not really about polynomial rings. Here is a generalization.

Let $A$ be a commutative $\mathbb{N}$-graded ring. Let $f \in A$ be a zero divisor. Then there is some $0 \neq a \in A$ homogeneous such that $a f = 0$.

Proof. Choose some $0 \neq g \in A$ of minimal total degree with $fg=0$. Let $f=f_0+f_1+\dotsc$ and $g=g_0+g_1+\dotsc+g_d$ be the homogeneous decompositions with $g_d \neq 0$. If $f g_d = 0$, we are done. Otherwise, we have $f_i g_d \neq 0$ for some $i$, and hence $f_i g \neq 0$. Choose $i$ maximal with $f_i g \neq 0$. Then $0=fg=(f_0+\dotsc+f_i)g=(f_0+\dotsc+f_i)(g_0+\dotsc+g_d)$ implies $f_i g_d = 0$. Then $f_i g$ has smaller degree than $g$, but still satisfies $f(f_i g)=0$ and $f_i g \neq 0$, a contradiction. $\square$

This may be applied to $A=R[x]$ with the usual grading. Hence, any zero divisor in $R[x]$ is killed by some element of the form $r x^n$ ($r \in R \setminus \{0\}$) and then also by $r$.

share|cite|improve this answer
why is degree of $f_ig$ smaller than degree of $g$ (in graded ring)? – Pham Hung Quy Dec 14 '14 at 14:11

This is the case of Armendariz Rings, which I studied in last summer briefly. It is an interesting topic.

A ring $R$ is called Armendariz if whenever $f(x)=\sum_{i=0}^{m}a_ix^i, g(x)=\sum_{j=0}^{n}b_jx^j \in R[x]$ such that $f(x)g(x)=0$, then $a_ib_j=0\ \forall\ i,j$

In his paper "A NOTE ON EXTENSIONS OF BAER AND P. P. -RINGS" in 1973, Armendariz proved that Reduced rings are Armendariz which is a nice generalization of your result.

Proof- Ler $fg=0$ and assuming $m=n$ is sufficient. We then have $$a_0b_0=0,\\ a_1b_0+a_0b_1=0 ,\\ \vdots \\a_nb_0+\dots +a_0b_n=0$$

Since R is reduced, $a_0b_0=0\implies (b_0a_0)^2=b_0(a_0b_0)a_0=0 \implies b_0a_0=0$.
Now left multiplying $a_1b_0+b_1a_0=0$ by $b_0$ we get $b_0a_1b_0=-b_0a_0b_1=0 \implies (a_1b_0)^2=a_1(b_0a_1b_0)=0 \implies a_1b_0=0$.
Similarly we get $a_ib_0=0\ \forall\ 1\leq i \leq n$.

Now original equations reduces to
$$a_0b_1=0\\ a_1b_1+a_0b_2=0\\ \vdots\\ a_{n-1}b_1+\dots +a_0b_n=0$$ and then by same process first we will get that $a_0b_1=0$ and then multiplying on left of $a_1b_1+a_0b_2=0$ by $b_1$ we get $a_1b_1=0$, and so on we will get, $a_ib_1=0\ \forall\ 1\le i \le n$...

Similarly, Repeating it we get $a_ib_j=0\ \forall\ 1 \leq i,j \leq n$. $\hspace{5.5cm}\blacksquare$

Some other examples of Armendariz Rings are-

  • $\Bbb{Z}/n\Bbb{Z}\ \forall\ n$
  • All domains and fields (which are reduced)
  • If A and B are armendariz , then $A(+)B$ in which multiplication is defined by $(a,b)(a',b')=(aa',ab'+a'b)$ is armendariz
  • Direct Product of armendariz rings
share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.